HOW TO TRANSLATE SCIENTIFICALLY: A CASE IN THE JOURNAL OF “MEDICINA” - I Made Juliarta (English Department, Faculty of Humanities, Udayana University, 2016)
This reasearch aimed at analyzing and discussing the technique or procedure applied bytranslator in translating text found in the journal medicina. There are some procedures oftranslation techniques found and applied by translator. Some of the translation techniquesapplied by the translator consisting of borrowing, transposition, equivalence, structure shift,unti shift, literal, calque, addition and substraction. It was the borrowing technique used inapplying the translation of terms which have been considered a part of respective TL. Unitshift is said as the change from word to group of word or in reverse. A different of modifierheadrule between SL and TL can occur in the structure shift. Equivalence and literaltranslation or words per word translation were found. It is important to apply the techniqueof calque which was reagarded as special kind of borrowing. There were the last twotechniques which were also found as unavoidably which is applied by translator. Applyingappropriate techniques in translating is needed in order the translation product can be reliableand acceptable for the reader.